2006
DOI: 10.1158/1078-0432.ccr-05-1084
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Inhibition by LY294002 Radiosensitizes Human Cervical Cancer Cell Lines

Abstract: Purpose: The phosphatidylinositol 3-kinase (PI3K) catalytic subunit is amplified in cervical cancers, implicating PI3K in cervical carcinogenesis. We evaluated the radiosensitizing effect of PI3K inhibition by LY294002 on clonogenic survival, growth characteristics, and gene expression in cervical cancer cell lines (HeLa and CaSki). Experimental Design: Cervical cancer cells were treated separately and concurrently with the PI3K inhibitor LY294002 (10 Amol/L) and radiation (2 Gy) with serial analysis of cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 26 publications
0
69
0
Order By: Relevance
“…Also, their conclusion that only increased HER2 expression associated with improved OS is quite an opposite conclusion to the previous paper (Nakano et al, 1997). In addition, Lee suggested that 'PI3K inhibition radiosensitises cervix cancer' in his recent publication (Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, their conclusion that only increased HER2 expression associated with improved OS is quite an opposite conclusion to the previous paper (Nakano et al, 1997). In addition, Lee suggested that 'PI3K inhibition radiosensitises cervix cancer' in his recent publication (Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 79%
“…Phosphoinositide-3-kinase catalytic alpha, involved in the PI3K/ AKT-signalling pathway, is known to be an oncogene associated with cervical cancer (Ma et al, 2000). In addition, the PI3K catalytic subunit is amplified in cervical cancer, and the inhibition of PI3K by LY294002 radiosensitises human cervical cancer cell lines (Lee et al, 2006). Therefore, we thought it would be worthwhile to investigate the components of PI3K/AKT pathway in cervical cancer.…”
mentioning
confidence: 99%
“…One factor known to increase tumor cell resistance to radiation, the importance of PI3K/AKT targeting for overcoming resistance of tumors to radiotherapy, has been tested in vitro and in vivo and the results indicate this cascade is a promising target (24)(25)(26). The activation of Akt plays a critical role in fundamental cellular functions such as cell proliferation and survival by phosphorylation of a variety of substrates (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway is a key regulator of cell growth through many downstream targets. Therefore, the PI3K inhibitor LY294002 can inhibit cell growth and cause apoptosis also in RCC cells (11)(12)(13)(14)(15) Previous reports showed that co-treatment with an HDAC inhibitor and a PI3K inhibitor was effective against ovarian cancer, cervical cancer, non-small cell lung cancer, colon cancer, chronic myeloid leukemia and cutaneous T-cell lymphoma by downregulating XIAP and Mcl-1 (16)(17)(18)(19)(20)(21). The PI3K-Akt pathway is well known to be upregulated in most RCC, but the combination of a PI3K inhibitor and an HDAC inhibitor has not been examined in RCC cells.…”
Section: Introductionmentioning
confidence: 99%